The Wrong Practice Of Anointing Oil In The Church According To James 5:14 A Theological Study - Sayangi Laia; Harman Ziduhu Laia; Daniel Ari Wibowo (Theological Journal Kerugma, 2020)
The practice of anointing with oil has been done in the church since the first century to the present. On the other hand, there are also churches which have refused to do this. The practice of anointing with oil has essentially lifted from James 5:14. This text has become one of one text in the New Testament which is quite difficult to understand and bring a variety of views. Not a few denominations of the church understand James 5:14 is wrong, even the Catholic church including in it. The increasingly incorrect practice of anointing in the church today, that can be believed can heal disease physically and a variety of other functions push back the author to check the text of James 5:14 in the exegesis. Studies the exegesis of the deep, which focuses on the contextual, grammatical-structural,